Methods for the Evaluation of Waste Treatment Processes - Hans-Joachim Gehrmann; Markus Hiebel; Franz-Georg Simon (Journal of Engineering)
Decision makers for waste management are confronted with the problem of selecting the most economic, environmental, and socially acceptable waste treatment process. This paper elucidates evaluation methods for waste treatment processes for the comparison of ecological and economic aspects such as material flow analysis, statistical entropy analysis, energetic and exergetic assessment, cumulative energy demand, and life cycle assessment. The work is based on the VDI guideline 3925. A comparison of two thermal waste treatment plants with different process designs and energy recovery systems was performed with the described evaluation methods. The results are mainly influenced by the type of energy recovery, where the waste-to-energy plant providing district heat and process steam emerged to be beneficial in most aspects. Material recovery options from waste incineration were evaluated according to sustainability targets, such as saving of resources and environmental protection.